Do high workload and job insecurity predict workplace bullying after organizational change?. Issue 1 (6th February 2017) - Spagnoli, Paola; Balducci, Cristian
Abstract : Purpose: Organizational change eliciting negative outcomes might play a role in the development of workplace bullying. The purpose of this paper is to examine the direct and the interaction effect of two particular negative outcomes of organizational change, such as high workload and job insecurity, on workplace bullying. Design/methodology/approach: Participants in the study were 134 Italian workers who had just experienced an organizational change. A multiple regression analysis, using the stepwise method, was conducted to test for whether workload, job insecurity, and their interactions predicted workplace bullying. Findings: Results show that high level of workload is related to workplace bullying; job insecurity is not directly related to workplace bullying; the interaction between high workload and job insecurity enhanced the risk for workplace bullying. In particular, when the level of job insecurity is high there is a stronger relationship between workload and bullying, compared to when the level of job insecurity is low. Research limitations/implications: The cross-sectional design applied does not allow inference on the causal relationships between the predictors and outcomes. Practical implications: In order to decrease the occurrence of bullying, managers should avoid that employees experience high workload after organizational change by carefully designing the reengineering process. Additionally, they should try to reduce, as far as possible, employee perceptions of job insecurity. Originality/value: The focus of the study is on the "survivors" after organizational change and on particular interaction of workplace bullying's causes that could extremely enhance the risk of the phenomena.